From hurdles to high performance: overcoming day-to-day challenges for successful clinical trials at sites - Gangurde, Nutan; Bagde, Deepak (International Journal of Clinical Trials, 2024)
Randomized clinical trials are fundamental in testing new drugs, medical devices and treatment protocols. They help to determine the efficacy and safety of new treatments, leading to medical innovations that can significantly improve treatment outcomes. Clinical trial sites are the engines that drive medical advancements, but they face numerous challenges in their day-to-day operations and impact the study outcome as well as data quality. Continuous improvement through research and innovation ensures that clinical trials are conducted more effectively, leading to better healthcare advancements and patient outcomes. Execution of clinical trial at the hospital site is a critical task and associated with the new challenges every day which may include patient recruitment, retention and compliance to the data collection. GCP compliance is a soul of clinical research and difficult task to comply with. GCP is a harmonized guideline accepted by most of the countries all across the globe.